Water as a typical component of historical manor parks of the Poltava Region (Ukraine) - Shevchenko, Liudmyla; Novoselchuk, Natalia; Shevchenko, Artem; Troshkina, Olena; Skorobohatko, Oleksii (Landscape Architecture and Art, 2024)
The article highlights the issue of formation of manor parks of Poltava Region in the 18th-19th centuries, one of the left-bank territories of Ukraine. The water elements of such parks, their functional role, aesthetic and artistic significance and influence on the formation of the landscape and compositional structure of manor parks are the main focus of this study. A number of methods used in the work – historical-theoretical, field survey, complex analysis – became important assistants in the research. Four stages of the development of courtyard parks have been identified. The first, early stage, is characterized by a combined compositional scheme based on regular and landscape methods of territory organization. The second stage is characterized by a gradual departure from clear regularity. Techniques of free landscape planning prevailed in the compositional solution of park areas. This extended not only to the palace territory, but also to the front of the palace. The third stage of manor park construction demonstrates the further improvement of the style of classicism, architectural and spatial composition of manor and park complexes and landscape compositional solutions. The fourth, final stage is characterized by the formation of manor and park complexes on small territories, a departure from external splendor and pomp. The relationship between reservoirs and manor-park complexes was revealed, depending on the landscape and hydrological characteristics of the territory, the size of the complexes, and the compositional idea of the authors of these objects. The aesthetic characteristics of manor parks with water features are revealed. These data are confirmed by the memories of visitors to the estates, given in the article. The role and place of water elements in the compositional and architectural and planning decision of manor parks is clarified. The significant importance of the reservoir was emphasized due to its inclusion in the representative part of the manor park, its location on the main compositional axis, and the use of various landscape techniques. They either opened the reservoir for the owners and visitors of the estates, or hid it in the thickets of woody vegetation, providing a visual view through the so-called “backstage”. The arrangement of artificial islands on these reservoirs served as an additional compositional technique. Green plantations on the islands created picturesque volumes against the surface of calm mirror water, the reflection of which emphasized its deep characteristics.